A 3D Physics‐Based Particle Model of the Venus Oxygen Corona: Variations With Solar Activity. Issue 5 (2nd May 2022) - Tenishev, Valeriy; Combi, Michael R.; Shou, Yinsi; Bougher, Stephen; Ma, Yingjuan
Abstract: Due to Venus not having a substantial planetary magnetic field the fast‐flowing solar wind plasma can propagate to regions close to the planet. Therefore, thermal atomic oxygen in the thermosphere, hot oxygen in the corona, and the resulting pickup oxygen ions are essential for determining the overall interaction of the planet with plasma of the ambient solar wind. To investigate this complex system, we have initiated a project where a combination of Venus Thermosphere General Circulation Model (VTGCM) and Adaptive Mesh Particle Simulator (AMPS) codes are used to determine the variability of the "hot" O corona depending on the solar conditions. Here we present the results of modeling Venus' oxygen corona using the VTGCM ionosphere/thermosphere and AMPS kinetic particle models. VTGCM produces a self‐consistent calculation of the thermosphere/ionosphere, providing the spatial distributions of the dominant species. That is further used in AMPS' modeling of Venus' exosphere (a) to specify the source of the newly created hot O atoms produced by dissociative recombination of O 2 + O_2^+ ions and (b) to account for thermalization of these energetic oxygen atoms as they propagate in the upper thermosphere. The altitude distribution of hot O calculated for the solar maximum conditions agree well with Pioneer Venus Orbiter observations of the oxygen corona. The modeling that we have performed for the solar minimum conditions indicates a decrease of the oxygen density in the corona by almost a factor of six compared to that at solar maximum. That is consistent with the non‐detection of the oxygen corona from Venus Express. As expected, the solar moderate case is between the solar maximum and minimum cases. Plain Language Summary: Here we present an investigation of the variability of Venus' extended oxygen corona. For that, we employ a combination of fluid modeling for simulating Venus' ionosphere and thermosphere and kinetic modeling of the source and transport of energetic hot O atoms in the thermosphere. We have found a good agreement of the model results with the Pioneer Venus Orbiter observations of the "hot" O corona. We also found that the oxygen density strongly depends on solar conditions and varies by a factor of six over a solar cycle. That explains why the extended oxygen corona was observed only at the solar maximum. The result presented in this paper will be a part of a later study of the planet's interaction with the ambient solar wind, where the corona model would be used to calculate the mass loading coefficient. Key Points: The density of Venus' extended oxygen corona varies almost by a factor of six of magnitude during a solar cycle Kinetic modeling reproduces PVO observations of Venus' "hot" oxygen corona when forward scattering of the energetic oxygen atoms is employed The strong dependence of the oxygen density in the corona from solar conditions suggested by results of our modeling is consistent with the non‐detection of the oxygen corona from Venus Express conducted at solar minimum conditions